The chain mediating effect of mindfulness and self-esteem in the relationship between leisure-time physical activity and academic burnout among college students - Yuge Tian; Shangjian Yang (Scientific Reports)
Abstract This study aimed to investigate the relationship between leisure-time physical activity and academic burnout among college students, and the mediating roles of mindfulness and self-esteem in the relationship, so as to provide a reference for alleviating academic burnout among college students. The study used the Physical Activity Rating Scale, the Mindful Attention Awareness Scale, the Self-Esteem Scale, and the Academic Burnout Scale to conduct a questionnaire survey to 629 college students (M = 19.6) through a convenience sampling method. The constructed chained mediation model was tested for path analysis, and mediation effects using SPSS 29.0. The results showed that leisure-time physical activity, mindfulness, self-esteem and academic burnout were significantly correlated with each other. The direct effect of leisure-time physical activity on college students’ academic burnout was not significant, but the indirect effect was significant. Mindfulness and self-esteem had significant mediating effects between leisure-time physical activity and academic burnout among college students, and the mediating effects consisted of the independent mediation of mindfulness and self-esteem and the chain mediating effect between them. Thus, enhancing leisure-time physical activity as an intervention to alleviate academic burnout among college students should focus on the effects on mindfulness perception and self-esteem. By enhancing the levels of mindfulness perception and self-esteem, leisure-time physical activity may play an important role in alleviating the growing academic burnout among college students.